Transformasi Motif Ragam Hias Pada Rumah Tradisional Bugis di Kabupaten Bone, Soppeng dan Wajo - Jayadi, Karta; Suyudi, Muhammad; Akmal, Muhammad Syafruddin (Innovative: Journal Of Social Science Research, 2024)
This study can be seen as an effort to preserve cultural heritage, particularly the various decorative motifs found in traditional Bugis houses in Bone, Soppeng, and Wajo regencies. Various decorative motifs can be found in different parts of traditional Bugis houses, each with its own meaning and significance. The aim of this research is to identify the various decorative motifs present in traditional Bugis houses in Bone, Soppeng, and Wajo regencies. It is also hoped that this research will clarify the philosophical meanings associated with these motifs, as well as their positions and placements. Additionally, understanding the transformation of the functions and positions of these decorative motifs in traditional Bugis houses is crucial. This understanding serves as a factor for stakeholders to identify these issues, so that these traditions can be better preserved and serve as a reminder to the social community. This research is a qualitative study, utilizing data collection techniques such as interviews, documentation, transcription, and literature study.